On the Message Dimensions of Vector Linearly Solvable Networks - Das, Niladri; Rai, Brijesh Kumar (IEEE communications letters, 2016)
It is known that there exists a network which does not have a scalar linear solution over any finite field but has a vector linear solution when message dimension is 2. It is not known whether this result can be generalized for an arbitrary message dimension. In this letter, we show that there exists a network that admits an m dimensional vector linear solution, where m is a positive integer greater than or equal to 2, but does not have a vector linear solution over any finite field when the message dimension is less than m.